Green Marketing Dynamics in the Food and Beverage Product Sector: A Bibliometric Analysis of the Influence on Consumer Loyalty - Judijanto, Loso; Sholikin, Ahmad; Agus Tapaningsih, Weni Indah Doktri; Desembrianita, Eva; Yusita, Helda (West Science Social and Humanities Studies, 2024)
This bibliometric study explores the evolution and dynamics of green marketing within the food and beverage industry, with a specific focus on its influence on customer loyalty. Utilizing VOSviewer for network visualizations, the research maps the interconnectedness of key themes and authors over a significant period, highlighting the transition from traditional sustainability practices to more sophisticated, consumer-focused strategies that integrate service quality, customer satisfaction, and relationship marketing. The study reveals an evolving landscape where foundational marketing principles merge with modern green marketing needs, emphasizing the importance of genuine, consumer-centric approaches in fostering customer loyalty. The findings advocate for an interdisciplinary approach in research and suggest directions for future studies to further examine the empirical impacts of green marketing strategies, the role of digital technologies, and the global scalability of these practices.